2020
DOI: 10.17159/2312-3621/2020/v33n1a3
|View full text |Cite
|
Sign up to set email alerts
|

Reading Trauma Narratives: Insidious Trauma in the Story of Rachel, Leah, Bilhah and Zilpah (Genesis 29-30) and Margaret Atwood's The Handmaid's Tale

Abstract: This article investigates the notion of insidious trauma as a helpful means of interpreting the story of Rachel, Leah, Bilhah and Zilpah as told in Genesis 29-30 that has found its way into the haunting trauma narrative of Margaret Atwood's The Handmaid's Tale.In the first instance, this article outlines the category of insidious trauma as it is situated in terms of the broader field of trauma hermeneutics, as well as the way in which it relates to the related disciplines of feminist and womanist biblical inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Growing research has begun to illustrate the differences between trauma experienced by men and women. By promoting the insidious trauma theory, which provides a scope of groups that have everyday social status, women then fall into the often-devalued characteristics inherited, which are different from those valued in power (Claassens, 2020). Studies have shown that women are particularly vulnerable to victimization through sexual and physical assault, especially while living on the streets or in shelters (Milaney et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Growing research has begun to illustrate the differences between trauma experienced by men and women. By promoting the insidious trauma theory, which provides a scope of groups that have everyday social status, women then fall into the often-devalued characteristics inherited, which are different from those valued in power (Claassens, 2020). Studies have shown that women are particularly vulnerable to victimization through sexual and physical assault, especially while living on the streets or in shelters (Milaney et al, 2020).…”
Section: Introductionmentioning
confidence: 99%